Study on LED Visible Light Communication based on Wavelength Division Multiplexing Technology - WANG Guang-ye; ZOU Nian-yu; WANG Jin-peng; LI Ping; CHEN Ai-lin; YU Fang-nan; MIAO Mei-yuan; GAO Ying-ming (Guangtongxin yanjiu, 2016)
In this paper,we first introduce the principle of LED based visible light communication system and wavelength division multiplexing technology.Then we design the system structure of real-time visible light communication link with wavelength division multiplexing technology based on Optisystem software.Under the direct modulation scheme,the transmission performances of NRZ and RZ modulation are studied,respectively.The effects of different data rates on the bit error rate and Qfactor of the system are analyzed.The performances of bit error rate at different transmission distance are also discussed.Finally,the feasibility and stability of the wavelength division multiplexing technology in the visible light communication system are verified.